A dual policy paradox: why have trade and immigration policies always differed in labor-scarce economies? - Timothy J. Hatton; Jeffrey G. Williamson (Institute for the Study of Labor (IZA), 2006)
Today's labor-scarce economies have open trade and closed immigration policies, while a century ago they had just the opposite, open immigration and closed trade policies. Why the inverse policy correlation, and why has it persisted for almost two centuries? This paper seeks answers to this dual policy paradox by exploring the fundamentals which have influenced the evolution of policy: the decline in the costs of migration and its impact on immigrant selectivity, a secular switch in the net fiscal impact of trade relative to immigration, and changes in the median voter. The paper also offers explanations for the between-country variance in voter anti-trade and anti-migration attitude, and links this to the fundamentals pushing policy.
Keywords: F22; J1; O1; 330; tariffs; immigration restriction; international policy; economic history; Außenhandelspolitik; Migrationspolitik; Vergleich; Wahlverhalten; Welt